2019
DOI: 10.1111/aje.12615
|View full text |Cite
|
Sign up to set email alerts
|

Epigaeic ant diversity and distribution in the Sandstone Sourveld in KwaZulu‐Natal, South Africa

Abstract: Ants are sensitive to habitat change and may be affected by disturbances, such as alien plant invasion. Alien plant invasion is associated with negative effects on the functioning of ecosystems and may have adverse impacts on biodiversity. The aim of this study was to determine the diversity of ground‐dwelling ants in Tanglewood and Giba Gorge Reserves in KwaZulu‐Natal Province, South Africa. Ants were sampled in the wet and dry seasons. Pitfall trap sampling was carried out in an intact grassland, forest and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…Examining the makeup and organization of functional groups in each analyzed environment revealed that the observed species turnover was primarily caused by replacing habitat specialists with generalists. Other studies in different land-use have demonstrated similar replacement of functional categories among habitats (Arnan et al, 2014;Hlongwane et al, 2019), which is consistent with the ndings of this study. As a result of these ndings, it is now clear that each habitat has a distinct ant assemblage with its unique set of resource requirements and optimal environmental conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Examining the makeup and organization of functional groups in each analyzed environment revealed that the observed species turnover was primarily caused by replacing habitat specialists with generalists. Other studies in different land-use have demonstrated similar replacement of functional categories among habitats (Arnan et al, 2014;Hlongwane et al, 2019), which is consistent with the ndings of this study. As a result of these ndings, it is now clear that each habitat has a distinct ant assemblage with its unique set of resource requirements and optimal environmental conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Parasyscia lamborni, Bothroponera crassa and Camponotus acvapimensis. Similar ndings have been reported by FotsoKuate et al (2015) in different vegetation types of Southern Cameroon, andHlongwane et al (2019) in the Sandstone Sourveld in KwaZulu-Natal, South Africa. Our ndings are consistent with those reported by MauriceKouakou et al (2018) in Côte d'Ivoire (West Africa), who identi ed the species Bothroponera crassa as one of the most abundant among the Ponerinae and corroborate with those reported by…”
supporting
confidence: 89%
“…In fact, there were five or fewer publications for all the ant species collected besides the common “tramp species” or urban pests, like Tapinoma sessile and Tetramorium immigrans ( Kamura et al 2007 , Uno et al 2010 ). Our systematic review of ant biodiversity surveys in different biomes over the last five years revealed a bias towards Tropical & Subtropical Grasslands, Savannahs & Shrublands (eight studies, Cross et al 2016 , Van Schalkwyk et al 2019 , Arcoverde et al 2016 , Lasmar et al 2020 , Dröse et al 2019 , Hlongwane et al 2019 , de Queiroz et al 2020 , Santoandré et al 2019 ). We found two studies on Tropical & Subtropical Moist Broadleaf Forests ( Lawes et al 2017 , Klunk et al 2018 ), one study on Tropical & Subtropical Coniferous Forests ( Cuautle et al 2016 ), three studies on Temperate Broadleaf & Mixed Forests ( Braschler and Baur 2016 , Helms et al 2020 , Heuss et al 2019 ), one study on Montaine Grasslands & Shrublands ( Jamison et al 2016 ), three studies on Mediterranean Forests, Woodlands & Scrub ( Adams et al 2018 , Catarinue et al 2018 , Flores et al 2018 ) and one study on Deserts & Xeric Shrublands ( Álvarez and Ojeda 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…To better demonstrate how much predation can be beneficial to producers, we can simulate leaf herbivory calculations. According to Hlongwane (2019), throughout the larval stage of Belenois solilucis, it consumes an average of 89 cm² of the soybean leaf area (varying between types of cultivar). Assuming that all predated eggs in this experiment generated larvae that devoured 89 cm²/individual leaf area, each location would suffer damage of 2.4m²/day of leaf area loss on average.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of planting in the landscape, on the other hand, significantly increases predation rates by winged predators (Groc et al, 2017), most likely because it is linked to the hypothesis of resource concentration (Hlongwane et al, 2019) and because it maintains an already regional set of species adapted to agrosystems. Nonetheless, it is essential to note that very high proportions of conventional planting in the landscape -above 31.2% of the landscape, as analyzed here -have had a detrimental impact on biodiversity and its services (Mauda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%